Monoclonal antibodies for the treatment of non-hematological tumors: a safety review. Issue 12 (2nd December 2018) - Corsini, Lidia Rita; Fanale, Daniele; Passiglia, Francesco; Incorvaia, Lorena; Gennusa, Vincenzo; Bazan, Viviana; Russo, Antonio
ABSTRACT: Introduction : The introduction of monoclonal antibodies (moAbs) into clinical practice revolutionized the treatment strategies in several solid tumors. These agents differ from cytotoxic chemotherapy for their mechanism of action and toxicity. By targeting specific antigens present on healthy cells and modulating immune system activity, these biological drugs are able to generate a wide spectrum of peculiar adverse events that can negatively impact on patients' quality of life. Areas covered : In this review, the main side effects associated with the use of moAbs have been described to show their incidence and current management strategies, which may drive clinicians in their daily practice. Expert opinion : The majority of these drugs represents an example of successful innovation, since they are able to induce a significant improvement of patients' survival and quality of life without any increase in related side effects as compared to standard cancer treatments. For this reason, they have become new milestones in personalized therapy for different non-hematological malignancies. With the increasing use of moAbs in treatment regimens, it is strongly recommended that clinicians are knowledgeable about the side effects associated with these agents, their management and monitoring, to optimize the clinical treatment of cancer patients.